1993
DOI: 10.1523/jneurosci.13-07-02965.1993
|View full text |Cite
|
Sign up to set email alerts
|

Selective distribution of kainate receptor subunit immunoreactivity in monkey neocortex revealed by a monoclonal antibody that recognizes glutamate receptor subunits GluR5/6/7

Abstract: A monoclonal antibody (4F5) was generated against a portion of the putative extracellular domain of glutamate receptor subunit GluR5. Western blot analyses and immunocytochemistry of transfected human embryonic kidney 293 cells confirmed that monoclonal antibody 4F5 was specific for GluR5, -6, and -7 (the three identified members of the kainate receptor subunit class), but did not recognize GluR1, -2, or -3 (the AMPA/kainate receptor subunit class). The antibody was subsequently used to examine immunocytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 93 publications
11
71
2
2
Order By: Relevance
“…Some were very intensely stained; others were more lightly stained. The cytoplasmic localization of kainate receptors in enteric neurons agrees with previous studies that have visualized these receptors in fixed and permeabilized central neurons, using C-terminal antibodies (Huntley et al, 1993). At least part of the internal labeling may represent receptor subunits in synthesis or in transport to and from the cell membrane, similar to the proposals for AMPA-selective glutamate receptor subunits (Wenthold et al, 1990).…”
Section: Kainate Receptor Subunit Immunoreactivity Is Found In Enterisupporting
confidence: 87%
See 1 more Smart Citation
“…Some were very intensely stained; others were more lightly stained. The cytoplasmic localization of kainate receptors in enteric neurons agrees with previous studies that have visualized these receptors in fixed and permeabilized central neurons, using C-terminal antibodies (Huntley et al, 1993). At least part of the internal labeling may represent receptor subunits in synthesis or in transport to and from the cell membrane, similar to the proposals for AMPA-selective glutamate receptor subunits (Wenthold et al, 1990).…”
Section: Kainate Receptor Subunit Immunoreactivity Is Found In Enterisupporting
confidence: 87%
“…To locate proteins in the tissue by immunocytochemistry, we exposed the preparations to PBS containing 0.5% Triton X-100 and 4% horse serum for 30 min to permeabilize the tissue and reduce background staining. Immunoreactivity was then demonstrated by incubating the tissues with affinitypurified rabbit polyclonal antibodies (24 -48 hr; 4°C) to GluR1 and GluR2/3 (0.5 g /ml; Petralia and Wenthold, 1992), EAAC1 (0.06 g /ml; Rothstein et al, 1993), GluR5/6/7 (Huntley et al, 1993), or NSE (1:3000; Polysciences, Warrington, PA); mouse monoclonal antibodies to calbindin (CBP; 1:100; Sigma) or nonphosphorylated neurofilament H (SM I-32; 1:500; Sternberger Monoclonals); or goat antibodies to calretinin (1:6000; Chemicon, Temecula, CA) (see Table 1). In most experiments, bound antibody was visualized by incubating tissues for 3 hr with indocarbocyanine (C y3)-labeled or FI TC -labeled species-specific secondary antibodies to IgG (diluted 1:4000; Jackson ImmunoResearch, West Grove, PA); however, SM I-32 immunoreactivity was demonstrated with the Elite kit (Vector Laboratories, Burlingame, CA) and visualized with diaminobenzidine (DAB substrate kit; Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…The use of antibodies recognizing GluR6/7 (Petralia et al, 1994), GluRs/6/7 (Huntley et al, 1993;Siegel et al, 1995), or KA2 subunits (Petralia et al, 1994;Roche and Huganir, 1995) revealed a similar distribution of glutamate receptor subunits and of [3H]kainate binding sites. In the rat and monkey hippocampus, the immunoreactivity with these antibodies occurs mainly in the hilus and in the CA3 subregion (Petralia et al, 1994;Siegel et al, 1995).…”
Section: Immunocytochemandtrymentioning
confidence: 93%
“…In the rat and monkey hippocampus, the immunoreactivity with these antibodies occurs mainly in the hilus and in the CA3 subregion (Petralia et al, 1994;Siegel et al, 1995). At the synaptic level, the localization of kainate receptor subunits appears to be principally at the postsynaptic membranes (Petralia et al, 1994;Huntley et al, 1993;Siegel et al, 1995). However, presynaptic KA2 subunits were also identified in nerve terminals of the rat cerebral and cerebellar cortex (Petralia et al, 1994).…”
Section: Immunocytochemandtrymentioning
confidence: 99%
“…Kainate receptors are densely distributed along cortical dendrites [7], namely, and might therefore require a critical amount of morphological substrate in order to display clearcut signs of plasticity. Furthermore, organotypic co-cultures -especially of the recently developed 'mega' variety -exhibit firing patterns which much more closely approximate the in vivo picture than do simpler preparations [9].…”
mentioning
confidence: 99%